Analisa Variasi Kecacatan pada Shower Hanger (Part C0205-Su_Im) dengan Metode One Way Anova di PT. Surya Toto Indonesia, Tbk - fredy dwi ibnu Saputra (Universitas Pamulang, 2020)
PT. Surya Toto Indonesia, Tbk is a company engaged in the field of Sanitary and Fitting. In an effort to maintain the quality of its products, PT. Surya Toto Indonesia, Tbk seeks to minimize the number of disabilities in each of its inspection units. For that we need a method of control and quality improvement to identify defects to the source of the cause. Based on the data of Quality Control (QC) at the Shower Hanger (Part C0205-SU_IM) from January to June 2016, there are three major defects that dominate: Scratch, Burrs, and Pit defects with cumulative percentage reaching 76.18 %. The results of the analysis conducted by the author using the method of One Way Anova (One Way Analysis of Variance), known the dominant cause that is in Mold and after the repair on the Mold there is a decrease in defect rate of 81.26%. From defect data in 2016 prior to improvement.